Correction: Corrigendum: Controlling hybrid nonlinearities in transparent conducting oxides via two-colour excitation - M. Clerici (Nature Portfolio, 2017)
Nature Communications 8 Article number: 15829 (2017); Published 9 June 2017; Updated 1 August 2017 An incorrect version of the Supplementary Information was inadvertently published with this Article, where the pump wavelengths for panels a and b were interchanged in the figure caption of Supplementary Fig.